THE INSECURE VIRUS CONTAMINATION TO TERRORISM IN SOCIETY 5.0 IN INDONESIA’S DIGITAL SPACE - Ali Ridho; Mahfuzah Saniah; Joko Prayudha S.; Idi Warsah (university Of islam, 2023)
The transformation of conventional mass media into digital has had an impact on human life in all aspects of life, especially patterns of thinking and social practices. Ironically, the public is not yet fully aware of the potential threats posed by digital media. The process of migrating to digital media makes the virtual world lose depth and accuracy in digesting accurate and accountable information. Mental health and terrorism are a small number of diseases that colonize and inhabit the digital world as if preparing to infect its users. This research uses a qualitative approach with a literature study model. The main data sources were obtained from fifty reputable national and international scientific journals and books. Meanwhile, supporting data was obtained from various digital and social media platforms, such as YouTube, websites belonging to the government of the Republic of Indonesia and the private sector, and social media popular among people in the industrial era 5.0. This article examines in more depth how digital media has contaminated its users on a psychological aspect and has become a symptom of an acute social illness. This study concludes that among the forms of digital media disease are acute internet addiction, cybercrime, pornography-sexual crimes, cyberbullying, ignoring others, FOMO, living without a society, culture without privacy, noise in silence, nervous, liking to show off, thirst for appreciation, like sensation-controversy, to radicalism-terrorism.